Maternal determinants of low birth weight- a record-based study from a tertiary care centre in central India - Nair, Parvati; Wadhva, Sarita; Ukey, Ujwala; Narlawar, Uday; Dabir , Aditi (International Journal Of Community Medicine And Public Health, 2023)
Background: Birth weight is a major determinant of child’s health and nutrition. There are various factors which determine birth weight like maternal age, parity, socio economic status etc. A new born weighing less than 2.5 kg is classified as a low birth weight (LBW) baby. Low birth weight can be prevented by improving health status and socio-economic status of the community, improving antenatal care and also by providing proper health education. Methods: A record-based study was carried out in a tertiary care facility of central India. Labour room records from January 2021 to December 2021 were reviewed. The details on birth weight, gender, gestational age, parity, and mode of delivery were obtained and recorded. The data obtained was entered in Microsoft office excel software. Statistical analysis was carried out with the help of open Epi. Results: Out of 4266 records which were studied 46.65% mothers were in the age group 21-25 years and 53.52% were multiparas. The proportion of LBW was found to be 41.30%. LBW was found to have a significant association between age of mother, parity, residence and gender of the baby. Conclusions: In this study, sociodemographic factors, maternal age and multiparity has contributed substantially to LBW. Hospitals should inform pregnant women about the importance of appropriate age at conception. It is high time to discuss the aftereffects of older maternal age in detail and to focus more on biological components underlying these associations.